Pengaruh Program Promosi dan Ketepatan Waktu Pengiriman Terhadap Keputusan Pembelian Konsumen (Studi Kasus: Layanan Pesan Antar Makanan Aplikasi ShopeeFood di Kota Semarang) - Oktaviano, Arya; Gustino, Arsha (Jurnal Etnik: Ekonomi-Teknik, 2023)
This study analyzes the influence of timely delivery and promotional programs on consumer purchasing decisions in Semarang City for ShopeFood, an e-commerce company’s food delivery mobile application. Shopee’s success in e-commerce does not automatically translate to dominance in the food delivery industry. ShopeeFood employs promotional programs like the Payday Promo and the Double Date Promo, offering substantial discounts that increase user enthusiasm and encourage purchasing decisions. This research explores consumer behavior in response to these promotions and timely delivery, with a focus on economic development in information technology and the digital economy. Data analysis methods used in this quantitative study include descriptive analysis and multiple linear regression analysis. Through those methods, it is found that both timely delivery and promotional programs do encourage consumers to purchase food delivery service through ShopeeFood platform. Consumers purchasing decision will also significantly increase when both promotional programs and service quality, particularly timely delivery, are executed simultaneously. These findings aim to to assist ShopeeFood management in developing effective marketing strategies to enhance consumer purchasing decisions.